Hard Fats Improve the Physicochemical and Thermal Properties of Seed Fats for Applications in Confectionery Products - Md. Jahurul Haque Akanda; Norazlina M.R.; Azzatul F.S.; Hasmadi Mamat; Jau Shya Lee; Norliza J.; Mansoor A.H.; Jinap Selamat; Firoz Khan; Patracia Matanjun; Md Zaidul Islam Sarker; Sharifudin Md Shaarani (Taylor & Francis, 2024)
Non-Indexed Publication